Gliṅ Ge sar skyes buʼi rnam thar las Dbus ʼchi bdag cham la phab paʼi lo rgyus : an episode from the legend of the mighty Gesar of Ling - Karma-raṅ-byuṅ-kun-khyab-phrin-las, Khenpo Kalu (Kandro, 1975)
An authored episode of the Gesar epic.